Effect of Feeding Corn Distiller’s Dried Grains with Solubles (cDDGS) on Egg Quality Traits in Commercial Layers - Sedmake, Ekta D.; Khose, K. K.; Manwar, S. J.; Gole, M. A.; Wade , M. R.; Wankhede, S. M. (International Journal of Livestock Research, 2018)
The present experiment was conducted involving 180 layer chickens (BV- 300) for period of 10 weeks. The birds were randomly distributed into 5 treatment groups T1 (Control), T2, T3, T4 and T5 having 4 replicates of 9 layer birds each. The birds in treatment group T1 fed basal ration as per the recommendation of BV-300 layer strain and treatment groups T2, T3, T4 and T5 were offered diets containing 5, 10, 15 and 20% corn DDGS replacing soybean meal. Egg weight in control group T1 was significantly (P<0.01) higher compared to all other groups. The shape index of eggs from treatment group T5 was significantly (P<0.05) higher as compared to control group. The control group T1 was recorded significantly (P<0.01) higher egg surface area as compared to all other DDGS supplemented groups. The albumin index from control group T1 was recorded significantly (P<0.05) highest as compared to treatment group T2 receiving diet at 5% corn DDGS. There was non-significant difference in all treatment groups for the yolk index, haugh unit and percent egg shell weight. The treatment groups from T2, T3, T4 and T5 recorded significantly (P<0.01) increased yolk colour score as compared to control group. The egg shell thickness from treatment group T5 was significantly (P<0.01) increased as compared to control group. It may be concluded that the inclusion of corn DDGS at 20 % in layer diets found to improve egg quality parameters such as shape index, yolk colour score and egg shell thickness which is beneficial for egg processing industry.